New psychoactive substances: Challenges - Crnić Katarina B.; Kovačević Mira N. (Srpsko lekarsko drustvo, 2020)
Introduction: The United Nation Office of Drugs and Crime (UNODC) defines "new psychoactive substances" (NPS) as substances for abuse that are not under the control of the 1961 Convention on Narcotic Drugs or the 1971 Convention on Psychotropic Substances, but may constitute the definition of a group of different substances, which have been developing very rapidly since 2000 and are difficult to identify due to frequent changes in pharmacological and toxicological properties.The health risk assessment of consumers has been insufficiently researched.The use of NPS is reaching epidemic proportions worldwide and poses an increasing danger to the individual and public health. There are several basic groups of NPS, according to their chemical composition and pharmacological properties. All NPS cannot be safely differentiated according to these groups, and their effects, potency and risk profile are not similar to the substances from which they are derived. The highest percentage of abused NPS is from the group of synthetic cathinones and synthetic cannabinoids. Clinicaly, NPS abuse is categorized as acute intoxications, which is more common, because NPS is most often used on certain occasions (outings, musical events) or as an addiction. Acute intoxications with different types of NPS are severe, with numerous mental and physical symptoms, often life-threatening and with fatal outcomes. Adequate diagnosis is uncertain, diagnostic laboratory tests for drugs are generally not applicable to NPS. Symptomatic internal medicine and psychiatric therapy are used in the treatment because there are no specific antidotes, except for the group of synthetic opioids, (naltrexone). Patients with more serious complications are taken care of in intensive care units. Addiction to certain types of NPS is diagnosed and treated according to the principles of treatment of addiction to already known drugs. Methods: The paper presents an overview of available foreign and domestic literature and experiences of various authors on the topic of NPS from the previous 10 years, as well as the latest reports of regulatory bodies in the USA and Europe, in charge of monitoring epidemiological data on NPS. Topic: The main goal of the paper is to draw the attention of the professional public to the problem of the epidemic wave of new psychoactive substances in the world, as well as significant amounts of knowledge and experience and developing new strategies for registration, monitoring, diagnosis and treatment of abuses and dependence on these substances. Conclusion: These facts impose the need to raise the vigilance of the health and legal system according to the presence of NPS on the market and the prevalence of use in the population, their health risks, as well as connecting with European organizations for monitoring NPS and developing new strategies for their control and prevention.